Experimental study of the isotope effect of the permeability in structural steels for fusion reactors: Eurofer and SS316 - María Urrestizala; Jon Azkurreta; Natalia Alegría; Igor Peñalva; Marta Malo; Carlos Moreno; David Rapisarda (Nuclear Materials and Energy, 2024)
The transport of hydrogen isotopes through the elements that make up a fusion reactor, and their corresponding interaction with these materials, have a direct impact on its operation. Consequently, it is essential to master in advance their transport parameters in the different materials proposed to constitute the elements that will compound the fusion reactors, and, consequently, this is one of the main lines of fusion investigation. For reasons of technology, safety and viability, it would be desirable to have the possibility of experimenting only with protium and, from these values, to extrapolate those of deuterium and, above all, tritium. To do so, the classical atomic theory establishes that the ratio of these parameters is inversely proportional to square root of their mass ratio. However, discrepancies have been detected, so its verification has become fundamental. For this reason, this study presents the analysis of a series of tests of permeability carried out at the Fusion Materials Laboratory (UPV/EHU) using protium and deuterium with some samples of SS316 and EUROFER steels, in order to contrast the isotope effect, as well as the variables that could influence its adjustment. The results show that 316 steels present an isotope effect much closer to the theoretical one, while EUROFER steels differ more, increasing their isotopic ratio of permeabilities with temperature. In both cases, the trends are in line with published results.